Long-lasting isothiazolinone-based biocide obtained by encapsulation in micron-sized mesoporous matrices - Mardones, Lucas Emanuel (2018)
The use of mesoporous silica materials as new hosts for stabilizing isothiazolinone-based biocides was investigated. Two types of porous matrices were synthesized: SBA-15 mesoporous silica and mesocellular siliceous foam (MCF). The physicochemical properties of the silicas (structure, textural properties) were evaluated by SEM, TEM, XRD and adsorption/desorption of N2 in order to determine their ability to encapsulate, stabilize and subsequently release a commercial biocide used for latex preservation (CMIT/MIT). CMIT/MIT consists of an aqueous solution of the active ingredients CMIT (5-chloro-2-methyl-4-isothiazolin-3-one) and MIT (2-methyl-4-isothiazolin-3-one), present in a CMIT/MIT: 3/1 wt ratio. It was observed that the biocide can be encapsulated in both silica frameworks without suffering structural damage. The SBA-15 support exhibits a lower adsorption capacity of biocide molecules than MCF, which may be attributed to both agreater MCF pore volume and pore size. MCF has less hindered diffusion causedby a short channel length, which facilitates the biocide access to the pores ofthe matrix. The long pore length of SBA-15 makes the diffusion of CMIT/MIT mixture more difficult. Biocide release tests in aqueous media indicated that the CMIT/MIT concentration in the leaching solution depends on the matrix nature, the smaller values being obtained when the ordered matrix was used. Additionally, biocide delivery could be delayed by increasing the working pH from 7 to 9. Results showed that biocide encapsulation allows maintaining a long-lasting release, even under alkaline conditions (pH 9), at which the hydrolysis of non-supported CMIT occur. Several release tests at different temperature (318, 323 and 328 K), were carried out for 20 days at pH 7. The biocide loading after the tests was reflected in the IR spectra, and it has been corroborated that biocide encapsulation allows retarding the fast thermal decomposition of CMIT.